MENDORONG LITERASI DIGITAL GURU MELALUI MANAJEMEN PENDIDIKAN: TINJAUAN LITERATUR - Nurhidayati, Rina; Thaufani, Argi (STKIP Pesisir Selatan, 2025)
The development of digital technology has had a significant impact on the world of education, particularly in how teachers structure, implement, and assess the learning process. This condition requires teachers to have digital literacy skills that not only focus on technical skills, but also include critical thinking, ethical awareness, and creativity in information management. This article aims to analyze the role of educational management in improving teachers' digital literacy through a literature study with a qualitative descriptive approach. The analysis was conducted using content analysis of various relevant academic sources for the period 2021–2025. The results of the study indicate that educational management plays a strategic role in three main dimensions: (1) the formulation of adaptive digital policies and curricula, (2) the provision and optimal utilization of technological infrastructure, and (3) the implementation of teacher training and professional development. These three aspects complement each other and emphasize that improving digital literacy is not only the responsibility of individual teachers, but also the result of a synergy of policies, support facilities, and structured managerial programs. Of this research lies in the integration of the three dimensions of educational management into a holistic conceptual framework, which has not been widely explored in studies of teacher digital literacy.